Functions and working - Reserve Bank of India (Bombay, 1958)
A Bulletin entitled Functions and Working of the Reserve Bank of India was first published in 1941. Since then, as a result of constitutional developments as well as continuous adaptation to the needs of a rapidly developing economy, a great many changes have taken place both in the structure of the Bank as well as in the scope of its functions. The Bulletin has, therefore, been entirely re written and is now presented to the general public in the hope that it will enable them to understand the broad working of an institution which is so closely concerned with their general welfare.
Keywords: Banks and banking